Endoscopic Management of Nonlifting Colon Polyps. (14th May 2013) - Friedland, Shai; Shelton, Andrew; Kothari, Shivangi; Kochar, Rajan; Chen, Ann; Banerjee, Subhas
Abstract : Background and Study Aims . The nonlifting polyp sign of invasive colon cancer is considered highly sensitive and specific for cancer extending beyond the mid-submucosa. However, prior interventions can cause adenomas to become nonlifting due to fibrosis. It is unclear whether nonlifting adenomas can be successfully treated endoscopically. The aim of this study was to evaluate outcomes in a referral practice incorporating a standardized protocol of attempted endoscopic resection of nonlifting lesions previously treated by biopsy, polypectomy, surgery, or tattoo placement. Patients and Methods . Retrospective review of patients undergoing colonoscopy by one endoscopist at two hospitals found to have nonlifting lesions from prior interventions. Lesions with biopsy proven invasive cancer or definite endoscopic features of invasive cancer were excluded. Lesions ≥ 8 mm were routinely injected with saline prior to attempted endoscopic resection. Polypectomy was performed using a stiff snare, followed by argon plasma coagulation (APC) if necessary. Results . 26 patients each had a single nonlifting lesion with a history of prior intervention. Endoscopic resection was completed in 25 (96%). 22 required snare resection and APC. 1 patient had invasive cancer and was referred for surgery. The recurrence rate on follow-up colonoscopy was 26%. All of the recurrences were successfully treated endoscopically. There was 1 postprocedure bleed (4%), no perforations, and no other complications. Conclusions . The majority of adenomas that are nonlifting after prior interventions can be treated successfully and safely by a combination of piecemeal polypectomy and ablation. Although recurrence rates are high at 26%, these too can be successfully treated endoscopically.